Tamoxifen as Empirical Treatment in Males with Primary Infertility and Normal Gonadotropic Hormonal Levels: A Prospective Study (Iraqi Journal of Medical Sciences, 2021)
Background: One of the most commonly employed medical therapies for idiopathic male infertility are antiestrogens. Tamoxifen as estrogen receptor blockers have been used as empiric treatments for male infertility, acting through blocking estrogen receptor at the hypothalamus and pituitary levels and so preventing the important negative feedback of estrogens to the pituitary and hypothalamus as a result that leading to gonadotropin releasing hormone (GnRH) stimulation and pulsatile release of luteinizing hormone (LH)/follicle-stimulating hormone (FSH).Objective: To assess tamoxifen role in the treatment of men with primary infertility who are normogonadotropic. as it is widely prescribed drug for that purpose as well as to evaluate possible patient’s criteria for a better response to tamoxifen.Methods: One hundred twenty-three patients with idiopathic primary infertility and normal FSH, LH, and testosterone serum levels were enrolled in this prospective study. All patients received 20 mg tamoxifen daily as a single dose for at least 3 months, and semen analysis (total sperm concentration, total number of progressive motile sperms and percentage of normal sperm morphology) as well hormones levels were evaluated, with the values being compared with those before treatment.Results: Overall, there was no statistically-significant improvement in semen parameters 3 months after treatment (P>0.05); however, patients with pretreatment lower normal FSH level of (1.7-6.85 mIU/ml) and those with pretreatment sperm concentration of (five to ten million per ml) showed statistically significant improvement in sperm concentration after tamoxifen therapy (p=0.044 and p=0.012 respectively). Conclusion: Tamoxifen is an acceptable treatment for idiopathic male infertility. A better response can be expected in patients with pretreatment lower normal FSH level of (1.7-6.85 miu/ml) and sperm concentration of 5-10 million per ml. It might be used as first line treatment to enhance sperm concentration, giving its availability and lower cost in comparison to other hormonal therapies.Keywords: Male Infertility, tamoxifen, empirical treatmentCitation: Al-Anbary LA. Tamoxifen as empirical treatment in males with primary infertility and normal gonadotropic hormonal levels: A prospective study. Iraqi JMS. 2021; 19(2): 230-236. doi: 10.22578/IJMS.19.2.12